IFN-γ, should not be ignored in SLE - Liu, Wenping; Zhang, Shumin; Wang, Jibo (Frontiers in Immunology, 2022)
Systemic lupus erythematosus (SLE) is a typical autoimmune disease with a complex pathogenesis and genetic predisposition. With continued understanding of this disease, it was found that SLE is related to the interferon gene signature. Most studies have emphasized the important role of IFN-α in SLE, but our previous study suggested a nonnegligible role of IFN-γ in SLE. Some scholars previously found that IFN-γ is abnormally elevated as early as before the classification of SLE and before the emergence of autoantibodies and IFN-α. Due to the large overlap between IFN-α and IFN-γ, SLE is mostly characterized by expression of the IFN-α gene after onset. Therefore, the role of IFN-γ in SLE may be underestimated. This article mainly reviews the role of IFN-γ in SLE and focuses on the nonnegligible role of IFN-γ in SLE to gain a more comprehensive understanding of the disease.